Developing Integrated Student Worksheet with 3D Geometry Media to Improve Second Grade Students’ Learning Achievements - Rachmawati, Yeni (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2025)
The purpose of the study is to develop of a three-dimensional media of pop-up book worksheet as learning media on geometry. The method of this study is Research and Development (R&D). The validity test was carried out by media and material experts using questionnaires. The effectiveness of learning media was measured based on the N-Gain value indicator from the pre and post-test results, as well as the teacher and student response questionnaire scores. Student learning interest is measured based on the questionnaire score of student learning interest. The test of the effectiveness of learning media was carried out at a public elementary school in Batu City. The results showed that the validation score of the media expert reached 96.66%, while the validation score of the material expert validation reached 90.76% with an average of 93.71%, which means that the learning media could be classified valid. The results of the analysis of the effectiveness of the media based on the N-Gain value of 0.009 (sig value <0.05), it can be concluded that there is a significant difference in the gain score, which means that the increase in the pre to post-test could be classified as high criteria. The scores for the questionnaire responses from teachers and students were 92.50% and 86.46%, both of which were very effective. The percentage of interest in learning reached 90.09% with very good criteria. Based on these indicators, it can be concluded that the Pop Up Book as a Learning Media and student’s worksheet is declared valid by media and material experts, is effectively used in learning and is able to generate interest in learning in the very good category.